Impact of Preventive Health Care on Indian Industry and Economy - Alka Chadha; Ali Mehdi; Garima Malik (Indian Council for Research on International Economic Relations (ICRIER), 2007)
In this study, the authors have tried to examine the empirical evidence on the relationship between preventive health care and labour productivity and corporate profitability. While doing so, they try to generate awareness on the positive role of preventive health care in boosting the corporate sector's performance and improving the country's economy. Toward the end, based on their findings, they offer recommendations for policymakers and corporate management to promote preventive healthcare practice among employees. The primary research undertaken for this study included an electronic survey of some of the most well-established companies in the country, as well as a field-cum-electronic survey with a sample of employees in Delhi and the National Capital Region. Preventive health care holds enormous promise for the competitiveness of Indian companies, and for the country's economy in the global arena. In an era when the service sector is gaining pre-eminence, the value of the individual employee has increased more than ever before. Employees with specialized skills are the focal point on whose well-being and performance the productivity of a company rests. In a highly competitive corporate environment, companies cannot afford the absence of their employees due to sickness, caused by a sedentary lifestyle, etc., or a poor performance at the workplace due to poor health. Both as part of their corporate social responsibility and to boost their profits, a number of firms are offering preventive health care facilities to their employees. And it is on their performance, productivity and profitability that India's growth potential and global competitiveness depends substantially. Unfortunately, while the corporate sector has been quick to realize the benefits of preventive health care, policy has lagged behind and we do not yet have fiscal or other incentives that encourage prevention. While public spending on health has stagnated at 0.9 per cent of the GDP since the mid-1980s, and the government per capita health expenditure is one of the lowest in the world (US7, as against US2,548 in the United States), the government should focus its limited resources towards the health of the poor, and provide tax exemptions to sections which can take care of their own health needs.
Keywords: I11; I18; O4; 330; preventive; executive; corporate health care; check-ups; employee wellness; lifestyle changes; health policy; fiscal incentives; Gesundheitsvorsorge; Gesundheit; Arbeitskräfte; Gesundheitspolitik; Gesundheitswesen; Indien